Faktor–Faktor yang Mempengaruhi Inflasi Provinsi di Sumatera - Siswoyo Siswoyo; Asrini Asrini (Universitas Batanghari, 2020)
The purpose of this study is to know and analyze inflationary developments, road infrastructure, government spending, provincial minimum wage and economic growth provincial in Sumatra. know and analyze the influence of road infrastructure, government spening, provincial minimum wage and economic growth provincial in Sumatra. This research uses descriptive analysis method to know the development of each research variables and quantitative methods by using panel data regression approach random effect. Based on the results of descriptive analysis of inflationary development fluctuate, road infrastructure stagnated and government spending,provincial minimum wage and economic growth incresed every year. While the result of regression of panel data with random effect approach variable of provincial minimum wage have positive and significant influence to inflation of provincial in sumatra. While road infrastructure, government spending, economic growth have no significant effect on provincial inflation in Sumatra.